2020
DOI: 10.1039/d0ra07682a
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable access to fully biobased epoxidized vegetable oil thermoset materials prepared by thermal or UV-cationic processes

Abstract: Beyond the need to find a non-toxic alternative to DiGlycidyl Ether of Bisphenol-A (DGEBA), the serious subject of non-epichlorohydrin epoxy resins production remains a crucial challenge that must be solved for the next epoxy resin generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…The ERHO-4.5, EGRP-5, and ERHO-6 were synthetized following the previously reported method. [28] Epoxidation conditions were adjusted for each vegetable oil in order to maintain the following molar ratio conditions C = C/Acetic acid/H 2 O 2 (35% w/w); 1/0.5/1.5eq with amberlite IR-120 loaded at 10 wt% with respect to (w.r.t) acetic acid and hydrogen peroxide weight. Briefly, the vegetable oil (1eq of double bonds), toluene, and the acetic acid (0.5eq w.r.t double bonds) were added to the reaction mixture.…”
Section: Synthesis Of Epoxidized Vegetable Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERHO-4.5, EGRP-5, and ERHO-6 were synthetized following the previously reported method. [28] Epoxidation conditions were adjusted for each vegetable oil in order to maintain the following molar ratio conditions C = C/Acetic acid/H 2 O 2 (35% w/w); 1/0.5/1.5eq with amberlite IR-120 loaded at 10 wt% with respect to (w.r.t) acetic acid and hydrogen peroxide weight. Briefly, the vegetable oil (1eq of double bonds), toluene, and the acetic acid (0.5eq w.r.t double bonds) were added to the reaction mixture.…”
Section: Synthesis Of Epoxidized Vegetable Oilsmentioning
confidence: 99%
“…[27] We also investigated and compared the thermomechanical properties obtained from either UV or hardenerfree thermal curing of different epoxidized vegetable oils (EVOs). [28] To the best authors' knowledge, previous work on cationic photocuring of bio-based thermosets has focused only on the curing kinetics and on the thermo-mechanical properties of the obtained networks. So, there remains a need for assessing the coating properties and for evaluating their exploitation in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…This work demonstrated the possibility to tune the thermomechanical properties of the EVO thermosets by carefully selecting the starting vegetable oil. Higher double bond content in the raw materials resulted in higher epoxy index and improved thermo-mechanical properties [ 65 ].…”
Section: Cationic Photocurable Bio-based Epoxy Monomersmentioning
confidence: 99%
“…Biolaminates are natural fiber-reinforced bio-based epoxy resins [ 1 , 2 , 3 ]. Vegetable oils obtained from soybeans and flaxseeds are suitable for producing epoxy groups with high functionality due to their relatively high iodine value and high unsaturated fatty acid content [ 4 , 5 , 6 ]. Recent evaluations have reported that bio-based epoxy resins synthesized from functionalized natural compounds may have comparable thermal and mechanical properties with commercial epoxy resins [ 2 , 4 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils obtained from soybeans and flaxseeds are suitable for producing epoxy groups with high functionality due to their relatively high iodine value and high unsaturated fatty acid content [ 4 , 5 , 6 ]. Recent evaluations have reported that bio-based epoxy resins synthesized from functionalized natural compounds may have comparable thermal and mechanical properties with commercial epoxy resins [ 2 , 4 , 6 , 7 , 8 , 9 , 10 , 11 ]. The three main components of plant fibers are cellulose, lignin, and hemicellulose, where cellulose is responsible for the inherent strength and stability of the natural fibers, whereas hemicellulose contributes to their structure [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%